Perkembangan Dan Pengaruh Dinasti Zhou Terhadap Kemajuan Peradaban Tiongkok Kuno Hingga Masa Modern (1045–221 SM) - Ardi Tri Yuwono (Lambung Mangkurat University, 2024)
One of the oldest civilizations in the world is located on the plains of China and developed into the period known as Ancient China. One of the dynasties that played a role in the Ancient Chinese period was the Zhou Dynasty (1045-221 BC), which succeeded in overthrowing the Shang Dynasty (1600-1045 BC). Historians say the Zhou Dynasty was very important in Chinese history because it played a major role in the formation of modern-day China. This research aims to understand the development and influence of the Zhou Dynasty on Chinese history, both past and present. This research applies historical methods in the process, as for the stages as follows: (1) heuristics; (2) criticism; (3) interpretation; and (4) historiography. The Zhou Dynasty began with the founding by King Wu Wang after overthrowing the Shang Dynasty. During the passage of time, the Zhou Dynasty implemented a feudal system by giving plots of land to nobles. At the end of the Zhou Dynasty, the nobles rebelled and inter-regional wars led to the collapse of the Zhou Dynasty. Although the Zhou Dynasty had collapsed, the Zhou Dynasty had left legacies, such as: (1) The mandate of heaven (tiānmìng); (2) Fēngjiàn; (3) Confucianism; (4) Taoism; and (5) The Book Art of War.